Uma arquitetura baseada em técnicas de Realidade Misturada para o treinamento do uso de próteses acionadas por tirantes para indivíduos com amputação de membros superiores - Lima, Diogo Aparecido Cavalcante de (2019)
Upper limb amputation is a traumatic process where the amputee needs to immediately begin the rehabilitation process in order to regain physical independence. Access to a prosthesis can provide quality of life. However, traditionally rehabilitation periods may take up to 12 months due to the difficulty of using the prosthesis. Usually, during treatment, users are frustrated due to the delayed training process and the emotional state caused by the recent amputation. Additionally, some amputees training initiatives through Virtual Reality (VR) and Serious Games have appeared in the literature. However, studies show that training environments that use Mixed Reality (MR) associated with serious games can provide a more realistic and engaging experience for its users. Given the facts presented, this dissertation proposes the development of an architecture in which MR techniques associated with an embedded system are used, in order to enable the training of people who will use the use of upper limb prostheses. For its validation, system functioning tests were used, and usability questionnaires were applied to rehabilitation professionals. In the end, it was realized that the proposed and implemented architecture was satisfactory to perform the suggested activities in the mixed training environment.